Determining Factors of the Relationship of Knowledge Management and Human Capital on Innovation Performance of Digital School - Budiarta, Kustoro; Hidayat, Ahmad; Lubis, Nurul Wardani; Hasyim, Diana (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to analyze the influence of knowledge management and human capital on digital school innovation performance and identify the impact of knowledge management on digital school innovation performance through human capital. This research used an ex post facto approach with 165 teachers from digital schools in Medan City as the research sample. Data was collected through a validated and reliable questionnaire. The data that has been collected is then analyzed using the Partial Least Square (PLS) approach with the help of Smart PLS software. The research results prove that knowledge management positively and significantly affects human capital, with a path coefficient value of 0.220, a statistical t-value of 2.595, and a p-value of 0.009. Knowledge management has a positive and significant effect on digital school innovation performance with a path coefficient value of 0.176, a t statistic of 2.203, and a p-value of 0.0208; human capital has a positive and significant effect on digital school innovation performance with a path coefficient value of 0.409, a t statistic value of 5.604 and a p-value 0.000 and knowledge management has a positive and significant effect on digital school innovation performance through human capital. Increasing knowledge management practices in schools can be an effective strategy for improving teacher innovation performance in the context of digital education.